Problematising Boundaries and 'Hierarchies of Knowledge' within European Anthropologies. Issue 2 (1st September 2020) - Testa, Alessandro
Abstract: Is European anthropology the product of a colonialist plot to gain intellectual hegemony? Was the epistemic posture of its main representatives in the past one of crypto-imperialism aimed at – and based upon – power, in the attempt to climb up the 'hierarchy of knowledge' and subjugate from its peak minor traditions of study? How can we think about the genealogy of Euro-anthropology (and its future progress) without necessarily capitulating to these narratives of powerism and to the grip of the radical post-colonial discourse, which has been growing mainstream of late? This piece seeks to briefly but piercingly address these pressing issues, while at the same time proposing a few viable routes around the resulting methodological impasses. It also represents the prolegomena to a longer and more substantial critique, which will be published later.